2019
DOI: 10.1109/access.2019.2901094
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Isoperimetric Graph Partitioning Problem

Abstract: Isoperimetric graph partitioning, which is also known as the Cheeger cut, is NP-hard in its original form. In the literature, multiple modifications to this problem have been proposed to obtain approximation algorithms for clustering applications. In the context of image segmentation, a heuristic continuous relaxation to this problem introduced by Leo Grady and Eric L. Schwartz has yielded good quality results. This algorithm is based on solving a linear system of equations involving the Laplacian of the image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 42 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…In [27], the power watershed framework was extended and a simple generic algorithm was proposed to calculate the limit of minimizers under some conditions. Other applications of the power watershed framework can be found in [16,15,40]. The methods described in [16,15,40] use power watershed framework to reduce the size of the graph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [27], the power watershed framework was extended and a simple generic algorithm was proposed to calculate the limit of minimizers under some conditions. Other applications of the power watershed framework can be found in [16,15,40]. The methods described in [16,15,40] use power watershed framework to reduce the size of the graph.…”
Section: Introductionmentioning
confidence: 99%
“…Other applications of the power watershed framework can be found in [16,15,40]. The methods described in [16,15,40] use power watershed framework to reduce the size of the graph. In this article, we propose to use power watershed framework for spectral clustering -by computing a Γ −limit of spectral clustering.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is worth noting that Algorithm 1 decomposes the cost function on the original graph into costs on smaller subgraphs. It is shown in [17,18,21,11,10,23,22,12] that the computation of said limit is easier than minimizing the original cost Q(x). In Sec 4, Sec 5, Sec 6 and Sec 7, it will be demonstrated that the quality of the segmentation is retained while reducing the computational cost.…”
Section: Power Watershed Optimization and Contrast Invariancementioning
confidence: 99%
“…This is because of the cost in Eq 20 is always non-negative (a graph Laplacian is a positive semi-definite [53]). For the relaxed constraints, the cost can be made arbitrarily close to zero (which would be the minimum cost) for every possible partition of the graph (see [22] for details). Hence an additional constraint is added i.e.…”
Section: Classic Approach To Isoperimetric Graph Partitioning For Image Segmentationmentioning
confidence: 99%
See 1 more Smart Citation